Navigating Time and Space in Population Studies
XII, 245 p.
Keywords: This book presents innovative approaches to long-standing questions about the diffusion of population and demographic behavior across space and over time, adding a spatial dimension to temporal analysis and a temporal element to spatial analysis. The studies collected here utilize newly-available historical data along with spatially and temporally explicit analytical methods to assess and refine core demographic theories and to pose new questions about mortality and fertility transitions, migration, urbanization, and social inequality. Covering a broad range of geographical settings and spanning time periods from the eighteenth to the twentieth century, the book reveals the complexity of factors involved in population processes as they simultaneously spread across space and unfold over time. It also presents a rich set of tools with which to explore, analyze, and test the spatial and temporal dynamics of these phenomena.